Healthcare Access Challenges and Facilitators for Back Pain Across the Rural-Urban Continuum in Saskatchewan, Canada: Cross-Sectional Results From a Provincial-Wide Telephone Survey - Katie Crockett; Stacey Lovo; Alison Irvine; Catherine Trask; Sarah Oosman; Veronica McKinney; Terrence McDonald; Nazmi Sari; Bertha Carnegie; Marie Custer; Stacey McIntosh; Brenna Bath (SAGE Publishing, 2023)
Background: Chronic back pain is a common musculoskeletal disorder, disproportionately affecting rural and Indigenous people. Saskatchewan has a relatively high proportion of rural and Indigenous residents; therefore, understanding barriers and facilitators to accessing healthcare are needed to improve healthcare service delivery. Methods: A provincial-wide telephone survey explored experiences and perceived healthcare access barriers and facilitators among 384 Saskatchewan residents who experienced chronic low back pain. Chi-squared tests were performed to determine if people who lived in urban versus rural areas differed in the proportion who had accessed services from various healthcare practitioners. T -test and Mann-Whitney U analyses were conducted to determine differences between urban and rural, and Indigenous and non-Indigenous respondents. Results: Of 384 residents surveyed, 234 (60.9%) reported living in a rural location; 21 (5.5%) identified as Indigenous. Wait times (47%), cost (40%), travel (39%), and not knowing how to seek help (37%) were the most common barriers for Saskatchewan residents seeking care, with travel being the only barrier that was significantly different between rural and urban respondents ( P  ⩽ .001). Not knowing where to go to access care or what would help their low back pain ( P  = .03), lack of cultural sensitivity ( P  = .007), and comfort discussing problems with health care professionals ( P  = .26) were greater barriers for Indigenous than non-Indigenous participants. Top facilitators (>50% of respondents) included publicly funded healthcare, locally accessible healthcare services, and having supportive healthcare providers who facilitate referral to appropriate care, with urban respondents considering the latter 2 as greater facilitators than rural respondents. Telehealth or virtual care ( P  = .013) and having healthcare options nearby in their community ( P  = .045) were greater facilitators among Indigenous participants compared to non-Indigenous respondents. Conclusions: Rural, urban, Indigenous, and non-Indigenous people report overlapping and unique barriers and facilitators to accessing care for chronic low back pain. Understanding perceived access experiences will assist in developing more effective care models for specific communities or regions.